What service should police provide? Towards a minimum policing standard - Bradford, Ben (Policing and society, 2025)
Police in England and Wales are under growing pressure to respond to multiple demands, with budgets and capabilities failing to keep pace. Alongside this, public scandals and wrongdoing are regularly revealed, debated and fed into reform programmes. Recognising these issues, we ask what members of the public really want from policing. Inspired by research on the Minimum Income Standard, this study aims to establish consensus on a set of activities and services that the police should be able to provide to everyone – a ‘minimum policing standard’. Three iterative rounds of focus groups conducted in four UK locations revealed broad agreement on the importance of responding to local problems, neighbourhood police presence and engagement and fair treatment, all of which were observed to be currently lacking. Generic crime priority lists were not seen to be useful for thinking about how police should respond to and protect communities. While participants emphasised the need for police to ‘pass things on’ to services better placed to provide solutions to problems such as drug misuse or homelessness, there was general agreement that an initial police response is necessary where risk of harm presents. Nonetheless, a widely shared view that the police should not be involved beyond first response in cases of threat to safety where no crime has been committed indicated a perceived boundary for police intervention. In conclusion, our research reveals considerable social consensus on what service police should provide and the minimum standards to which a police service should adhere.